Temporal changes in environmental health risks and socio-psychological status in areas affected by the 2011 tsunami in Ishinomaki, Japan - Makita, K.; Inoshita, K.; Kayano, T.; Uenoyama, K.; Hagiwara, K.; Asakawa, M.; Ogawa, K.; Kawamura, S.; Noda, J.; Sera, K.; Sasaki, H.; Nakatani, N.; et al. (Canadian Center of Science and Education, 2013)
On March 11 2011, a tsunami caused by a magnitude 9.0 earthquake devastated the northeastern coast of Honshu, Japan.The present study was conducted to assess environmental health risks of the areas affected and socio-psychological status of the dislocated people in Ishinomaki. Samples of sludge, water, flies and rodents were collected in 20 urban neighborhood associations affected by the tsunami in July and August 2011, and in August 2012. A socio-psychological survey was conducted in two urban and one rural temporary housing complexes in 2012. Animal feed concentrates and fish from damaged factories were scattered along the coast which caused a strong odor and great number of flies. Removal of fish and feed along with spraying insecticides reduced the odor and the number of flies by August 2011. The sludge and water samples contained potentially hazardous bacteria, but none were highly pathogenic. Heavy metals in sludge were not in alarming quantities. A rodent was captured in one unit in August 2011, and monitoring in two units found that the log number of rodents captured increased significantly over time (slope=0.08, p = 0.005). In temporary housing complexes, those who originally lived in rural fishing villages wished to return to their homes more (64.2%, 9/14) than in urban areas (30.6%, 11/36, p = 0.06). Risk factors for depression included absence of friends (p = 0.011) or trusted person to counsel in the housing complexes (p = 0.003) and illness of the respondent or a family member (p = 0.003). In conclusion, overall environmental health risk was acceptable for living, and monitoring of rodents population was recommended. In addition, psychological and economical support was needed for evacuees in temporary housing complexes.